2013
DOI: 10.1002/14651858.cd004453.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal surgical incisions for caesarean section

Abstract: The Joel-Cohen incision has advantages compared with the Pfannenstiel incision. These are: less fever, pain and analgesic requirements; less blood loss; shorter duration of surgery and hospital stay. These advantages for the mother could be extrapolated to savings for the health system. However, these trials do not provide information on severe or long-term morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 29 publications
1
63
0
1
Order By: Relevance
“…The PRISMA flow diagram is shown in addendum 3 (Key Question B). Six systematic reviews have compared midline laparotomies to alternative incisions [26,27,31,36,38,61], but only two were considered High Quality [26,27]. A recent systematic review by Bickenback et al [26] compared midline, transverse (including oblique) and paramedian incisions.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram is shown in addendum 3 (Key Question B). Six systematic reviews have compared midline laparotomies to alternative incisions [26,27,31,36,38,61], but only two were considered High Quality [26,27]. A recent systematic review by Bickenback et al [26] compared midline, transverse (including oblique) and paramedian incisions.…”
Section: Resultsmentioning
confidence: 99%
“…The technique offers a variety of advantages, including a more aesthetic cosmetic appearance, less postoperative pain, rapid recovery, and lower incisional hernia rates (2). There have been various studies evaluating complication rates, bleeding levels, operative times, and adhesion formation related to Pfannenstiel incisions (3). Maternal morbidity and complication rates are even more pronounced in repeat cesarean deliveries, especially after a third operation (4).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, SC begins through a Pfannenstiel incision, but in a 2013 review Joel-Cohen incision was found to be superior to Pfannenstiel incision in terms of postoperative outcomes [12]. Performing a bladder flap was found to be associated with greater (1 g/dl vs 0.5 g/dl) change in Hb levels compared with direct incision 1 cm above the bladder fold [13].…”
Section: Discussionmentioning
confidence: 99%